Emerging technologies in virtual learning environments - Becnel, Kim (IGI Global, 2019)
"This book provides relevant theoretical frameworks and the latest empirical research findings in virtual learning environments. It also identifies well-defined problems where innovative technologies can support successful solutions and subsequently determines the efficacy of effective virtual learning environments"--